2017
DOI: 10.1038/tp.2017.40
|View full text |Cite
|
Sign up to set email alerts
|

Instability of default mode network connectivity in major depression: a two-sample confirmation study

Abstract: Major depression is associated with altered static functional connectivity in various brain networks, particularly the default mode network (DMN). Dynamic functional connectivity is a novel tool with little application in affective disorders to date, and holds the potential to unravel fluctuations in connectivity strength over time in major depression. We assessed stability of connectivity in major depression between the medial prefrontal cortex (mPFC) and posterior cingulate cortex (PCC), key nodes in the DMN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
114
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(128 citation statements)
references
References 43 publications
10
114
1
3
Order By: Relevance
“…We found that the entropy associated with the FN-DMN-Str-SN state was significantly decreased in patients in neutral mood. This indicates a higher predictability of occurrence (Wang, 2008) of this FC state in rrMDD patients, supporting the idea that this brain state occurs in a less flexible manner.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…We found that the entropy associated with the FN-DMN-Str-SN state was significantly decreased in patients in neutral mood. This indicates a higher predictability of occurrence (Wang, 2008) of this FC state in rrMDD patients, supporting the idea that this brain state occurs in a less flexible manner.…”
Section: Discussionsupporting
confidence: 70%
“…Interestingly, previous studies in MDD have also found increased dynamic FC in areas overlapping with the FN‐DMN‐Str‐SN state: between the frontoparietal network and DMN (Kaiser et al, ) within the DMN (Wise et al, ) and between DMN (MPFC) and the insula (Kaiser et al, ); related to levels of self‐report rumination (Kaiser et al, ). This suggests that dynamic changes in FC in these areas might be particularly important for depression and a ruminative thinking style.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…comparisons. An early MDD study (7) found that DMN FC was positively correlated with current episode duration but this was not confirmed subsequently (9,25). We conclude that illness duration is likely unrelated to DMN FC.…”
Section: Discussionmentioning
confidence: 61%
“…We have found that trajectories of intra-cortical myelination in fronto-striatal systems are related to individual differences in compulsivity and impulsivity (Ziegler et al, 2018). It is also noteworthy that both the default mode network (Wise et al, 2017) and cortico-subcortical connectivity (Heller, 2016) have been previously implicated in the pathophysiology of major depressive disorder.…”
Section: Discussionmentioning
confidence: 72%